Potensi Pengembangan Medical Tourism di Rumah Sakit Indonesia - Yefta Yefta; Sri Retno Widyorini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Medical tourism is a new form of tourism and medical services by getting health services according to expectations to a certain area. In an effort to develop the health system and competition as well as the impact of health globalization, it is possible that medical tourism will lead to intense competition between hospitals in providing quality services and superior service products provided by these hospitals in attracting patients to come for treatment. Assessing the potential for the development of medical tourism in Indonesia and analyzing government regulations on the development of a medical tourism strategy in Indonesia. The method used is normative juridical, or legal research conducted by examining legal literature as primary material. Some things that must be considered in developing hospitals in Indonesia that have the potential to develop medical tourism services are tariffs, service quality, hospital accreditation, marketing, access to treatment from the aspect of transportation, availability of health workers and types of treatment. The central government, the ministry of health and local governments as policy or regulatory makers in terms of medical tourism in Indonesia play an important role. There needs to be regulations or policies that regulate matters related to medical tourism so that it is not just a discourse.